Pengaruh Self-Esteem dan Dukungan Sosial Terhadap Optimisme Masa Depan Anak Jalanan di Rumah Singgah Jakarta Selatan - Multasih, Endang; Suryadi, Bambang (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2013)
The purpose of this study is to examine the effect of self-esteem and social support toward theoptimism for future life of street children‟s at shelter (Rumah Singgah) South Jakarta. Thisstudy is also aimed at identifying the contribution of self-esteem and social support toward theoptimism for future life of street children. This study applied quantitative method usingmultiple regression for data analysis. The population of this study is 400 street children andthe sample size is 250 street children. The sample size consisted of 173 (69,2%) males and 77(30,8%) females, aged form 12 to 18 years. The sample of this study was selected using nonprobability sampling technique. In collecting the data, this study used three instruments. Theyare optimism for future life, self-esteem, and social support in the form of Likert scale model.The findings of the study indicate that there is significant effect of self-esteem and socialsupport toward the optimism for future life of street children with the significance value at0,000 (p > 0,05). The R-square (R2) value is 0,286 which means that about 28,6% of theoptimism for future life of street children is determined by the self-esteem and social support.